Synthesis of three-dimensional matrices based on collagen–pectin–polyacrylate grafted copolymers using the RbTe1.5W0.5O6 photocatalyst - Semenycheva, L. L.; Prodaevich, V. V.; Rumyantseva, V. O.; Fukina, D. G.; Koryagin, A. V.; Valetova, N. B.; Smirnova, O. N.; Suleimanov, E. V. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2025)
The development of new promising materials of three-dimensional structure from available bioresorbable, biointegrable and biocompatible polymers is in demand and relevant in connection with the intensive development of regenerative medicine. In this work, hydrogels of the grafted copolymers of methyl methacrylate/butyl acrylate onto a mixture of collagen and pectin were obtained during photocatalysis in the presence of a complex oxide RbTe 1.5 W 0.5 O 6 . The characteristics of the synthesis products were obtained by gel penetrating chromatography, elemental analysis, electron microscopy, and biological biocidality tests. The collagen content in an amount of less than 40%, the microstructure of the polymer in the form of a fine-mesh, and the biocidity of the sample films were established. The polymer product was identified on the catalyst surface after the separation of the oxide powder from the aqueous dispersion. The main advantage of such materials is the unique combination of properties of their components assembled into a specific structure. The advantages of the obtained material include, among other things, the environmental advantage of the initial components - natural renewable raw materials: collagen was isolated from cod processing waste, pectin from fruit and vegetable processing waste.